2023
DOI: 10.1088/1741-2552/acc75f
|View full text |Cite
|
Sign up to set email alerts
|

Auditory nerve responses to combined optogenetic and electrical stimulation in chronically deaf mice

Abstract: Objective. Optogenetic stimulation of the auditory nerve offers the ability to overcome the limitations of cochlear implants through spatially precise stimulation, but cannot achieve the temporal precision nor temporal fidelity required for good hearing outcomes. Auditory midbrain recordings have indicated a combined (hybrid) stimulation approach may permit improvements in the temporal precision without sacrificing spatial precision by facilitating electrical activation thresholds. However, previous research h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Optogenetic stimulation rates are limited by opsin kinetics, with the H134R variant used in this study exhibiting a relatively slow closing time of 18 ms that limits the rate at which stimuli can be applied ( Nagel et al, 2005 ). Long-term high rate optogenetic stimulation is less reliable compared to electrical stimulation, and the response size decreases over the duration of the pulse trains, as shown in the auditory system ( Hart et al, 2020 ; Thompson et al, 2020 ; Ajay et al, 2023 ). However, when optogenetic stimulation is combined with electrical stimulation, the reliability of firing increases ( Hart et al, 2020 ; Thompson et al, 2020 ) and can be ‘tuned’ to have response properties that are more like electrical responses or more like optical responses by adjusting the ratio of optical and electrical components of the combined stimulus ( Ajay et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Optogenetic stimulation rates are limited by opsin kinetics, with the H134R variant used in this study exhibiting a relatively slow closing time of 18 ms that limits the rate at which stimuli can be applied ( Nagel et al, 2005 ). Long-term high rate optogenetic stimulation is less reliable compared to electrical stimulation, and the response size decreases over the duration of the pulse trains, as shown in the auditory system ( Hart et al, 2020 ; Thompson et al, 2020 ; Ajay et al, 2023 ). However, when optogenetic stimulation is combined with electrical stimulation, the reliability of firing increases ( Hart et al, 2020 ; Thompson et al, 2020 ) and can be ‘tuned’ to have response properties that are more like electrical responses or more like optical responses by adjusting the ratio of optical and electrical components of the combined stimulus ( Ajay et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term high rate optogenetic stimulation is less reliable compared to electrical stimulation, and the response size decreases over the duration of the pulse trains, as shown in the auditory system ( Hart et al, 2020 ; Thompson et al, 2020 ; Ajay et al, 2023 ). However, when optogenetic stimulation is combined with electrical stimulation, the reliability of firing increases ( Hart et al, 2020 ; Thompson et al, 2020 ) and can be ‘tuned’ to have response properties that are more like electrical responses or more like optical responses by adjusting the ratio of optical and electrical components of the combined stimulus ( Ajay et al, 2023 ). Reliable control of neuromodulation would be essential to treat a condition such as pain, so keeping the optical stimuli near threshold helps to maintain the responses during repetitive stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to transgenic animals, delity at 100 pps for H134R was signi cantly lower, possibly as a result of the poorer quality and/or quantity of opsin expression in transduced animal models 5 . Studies have shown that improving tra cking to the plasma membrane improves activation thresholds and the reliability of responses at high stimulation rates.…”
Section: High-rate Stimulationmentioning
confidence: 94%